2000
DOI: 10.1016/s0022-5347(05)67513-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Case Matched Comparison of Hand Assisted Laparoscopic and Open Surgical Live Donor Nephrectomy

Abstract: Laparoscopic live donor nephrectomy appears to be a safe and effective alternative to open donor nephrectomy. Indexes of patient recovery suggest patient morbidity similar to that reported following standard laparoscopic donor nephrectomy and significantly less than after open nephrectomy. Improvement in operative time in the first 10 cases suggests that hand assistance "shortens" the learning curve, which might encourage more surgeons to offer laparoscopic live donor nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
3
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 8 publications
5
105
3
6
Order By: Relevance
“…A review of previously published series (8)(9)(10)(16)(17)(18) showed that operative times ranged from 183 to 230 min for laparoscopic donor nephrectomies, and from 183 to 213 for open donor nephrectomies. Estimated blood loss ranged from 122 to 266 mL for laparoscopic procurements, and from 192 to 408 mL for open approaches.…”
Section: Patient #5mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of previously published series (8)(9)(10)(16)(17)(18) showed that operative times ranged from 183 to 230 min for laparoscopic donor nephrectomies, and from 183 to 213 for open donor nephrectomies. Estimated blood loss ranged from 122 to 266 mL for laparoscopic procurements, and from 192 to 408 mL for open approaches.…”
Section: Patient #5mentioning
confidence: 99%
“…Laparoscopic live donor nephrectomy has been demonstrated to have several advantages when compared with open donor nephrectomy. They include but are not limited to shorter hospitalization, decreased pain measured by reduced analgesic requirements, an increased willingness of potential donors to undergo the procedure, and an earlier return to employment and full activities (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Gill et al [2] reported for the Wrst time of a retroperitoneoscopic approach to donor nephrectomy and autotransplantation where successful allograft outcome was achieved without vascular complications. Extensive data have been published showing that conventional laparoscopic and retroperitoneoscopic techniques for donor nephrectomy have a similar complication rate [3][4][5]. Retroperitoneoscopy provides two major advantages: Wrst, it oVers a quick access to the blood vessels comparable to the open approach and second, it has no interference with bowel, liver, or abdominal adhesions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated an improvement of donor outcome by means of minimally invasive techniques [4][5][6][7]. Furthermore, there is evidence that endoscopic minimalinvasive kidney donation can increase the number of kidney donations because of shorter hospital stay, earlier return to work, good cosmetic outcome and better overall patient satisfaction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In many centers, laparoscopic donor nephrectomy has reduced the morbidity of kidney donation and thereby encouraged living donors to donate (22)(23)(24)(25)(26). Laparoscopic donor nephrectomy reduces the postoperative convalescence time and enables donors to return to work quickly (22,24,25).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%